PENGARUH TINGKAT PENDIDIKAN, MASA KERJA DAN GOLONGAN KEPANGKATAN TERHADAP KINERJA PRAJURIT MELALUI MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Nunik Puji Rahayu; M Yusuf Qomaruddin (Institut Agama Islam Negeri (IAIN) Palopo, 2022)
The purpose of this study was to determine the effect of education level, years of service, and rank on the performance of Kodim 1403 Palopo soldiers mediated by Organizational Citizenship Behavior. The distribution of questionnaires using primary data and using an explanatory research design to determine the relationship between a number of variables. Respondents in this study were all 1403 Palopo Kodim Soldiers who were in Palopo City with saturated samples, by distributing questionnaires. The analysis used is multiple linear regression with SPSS and SEM PLS applications. Data analysis shows that the level of education, years of service, and rank have a direct but not significant effect on the performance of soldiers at Kodim 1403 Palopo. The level of education, years of service, and rank groups directly affect the Organizational Citizenship Behavior of the 1403 Palopo Kodim Soldiers. The level of education affects the performance of the Kodim 1403 Palopo Soldiers indirectly. Term of service does not significantly affect the performance of the 1403 Palopo Kodim Soldiers. Rank group has a negative effect on the performance of Kodim 1403 Palopo Soldiers through Organizational Citizenship Behavior.